Implementation Of Business Strategies With SWOT For Food Traders At Bungkul Park, Surabaya - Yuliatin Ali Syamsiah; Naniek Ratni Juliardi A.R. (Tibuana, 2022)
Small and medium Enterprises (SMEs) are a group of one of the largest economic actors in the Indonesian economy and have proven to be a safeguard for the national economy in times of crisis and also create sizable job opportunities for domestic workers, thus greatly assisting efforts to reduce unemployment caused by difficulties looking for jobs. This research is classified into qualitative research. Respondents were taken using purposive sampling technique. The method used is analysis using SWOT (Strengths, Weaknesses, Opportunities, and Threats). The results of research with SWOT analysis show that in managing finances, they still use traditional records, in products they still use recipes for the taste and quality of food and beverages, in promotions they are passive in waiting for consumers, strategic locations and neatly arranged.